Penegakan Hukum Terhadap Tindak Pidana Pembakaran Hutan Guna Pembukaan Lahan(Perspektif Hukum Indonesia dan Hukum Islam) - Wibawa, Aziz Kurnia; , Mutimatun Ni'ami, S.H., M.Hum (2016)
The presence of Act No. 32 of 2009 on the Environmental Protection and Management along with any Act on another sectoral has not carried out optimally yet as the facts. In Islamic law the act of forest burning is prohibited by syara', hence the rules on penal sanctions against the perpetrators is regulated in it. In this thesis there exists two problematics: how the law enforcement against forest burning crime to clear the land for new plantation in the perspective of Indonesian Law is and how the law enforcement against the forest burning crime to clear the land for new plantation in the perspective of Islamic law is. Researcher uses juridical normative method in the form of inventorizing positive law, as well as discovery (legal) in concreto which is feasible to complete a particular case. Law enforcement against forest burning has been regulated in the Act of Environmental Protection and Management ranging from administrative law enforcement means, a means of civil law enforcement and criminal law enforcement means. On the other hand, the forest fire arsonists are regulated in the category of jarimah ta'zir in Islamic law, where its provisions are submitted to the authorities (ulil amri) which in this case is The Judge.